Sketching : the basics - Eissen, Koos; Steur, Roselien (Amsterdam : BIS Publishers, 2011)
The sequel, or more accurately, prequel, to the bestseller 'Sketching'. It explains the rudiments of learning to draw both clearly and comprehensively using step-by-step illustrations, examples and strategies
1. Sketching in design -- 2. Drawing approach -- 3. Viewpoint -- 4. Sketching progress -- 5. Expressing colour and materials -- 6. Fast and fearless -- 7. Product context
Includes bibliographical references (p. 200)
Keywords: Drawing -- Technique; Product design